Clamshells Energy Melalui Metode Elektrolis Dalam Memenuhi Kebutuhan Listrik Masyarakat Pesisir - Zulkifly Rumba Anung Singku (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX, 2019)
All activities are carried out essentially in need of human energy. The availability of energy including electricity is a very important element, as well as the need to support sustainable national development. Related problems of energy, an area that has not been much teraliri power is the coastal region. Indonesia is an archipelago geographically with two thirds of the vast ocean bigger than the Mainland. The existence of the beach at nearly every island in Indonesia (± 81,000 km) which made Indonesia as the country with the second longest coastline in the world. At UU RI No. 27 Year 2007 about management of the coastal areas and small islands, in law is intended regarding planning, utilisation, supervision, and control of the Natural Resources of coastal and small islands. People who live in the island, it is very far from the power plant, owned by PLN. Data from the Ministry of Internal Affairs of INDONESIA declared Indonesia has 17,504 Islands, of which there are 6000 island inhabited community. With the new alternative energy, expected to coastal communities can support the Nawa. Electrical energy derived from shells (Clamshells) is able to be used as alternative energy needs, overcome electrical get hooked for coastal communities. Coastal areas are likely to be met by waste shells, shells even just be discarded waste not utilized by the community around the beach and just left. Shells which is a compound of CaCO3 can be extracted through methods of electrolysis is reacted with a compound with HCl in order that formed the compound CaCl2. The compound result of the reaction of then in electrolysis to get the compound Ca. Reactions that happen to produce ions that can produce electricity with Electrodes. From the results of this research are able to create alternative energy, while reducing the pollution of waste shells on the coast are able to produce a sufficient amount of energy and marine resources to support economic development and the welfare of fishermen coastal communities.